ModMan: An Advanced Reconfigurable Manipulator System With Genderless Connector and Automatic Kinematic Modeling Algorithm - Yu, Alchan; Moon, Deaho; Ha, Tunhyoung; Kang, Sungchul; Lee, Woosub (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
With the current trend of dwindling life cycle of production, necessity of systems with high-adaptability is on the rise. With their high adaptability and easy maintenance, reconfigurable manipulators are strong candidates to replace conventional non-reconfigurable manipulators in such trend. However, most of existing reconfigurable robots are designed for non-industrial use and remained in laboratory level because of their low accuracy and low mechanical/electrical capacity. In this letter, we present our newly developed manually reconfigurable manipulator, ModMan, equipped with genderless connectors which feature high mechanical/electrical capacity and multi-DOF modules, which are to increase the number of possible configurations while minimizing loss of manipulator performance. An automatic kinematic modeling algorithm for reconfigurable manipulators is also presented to deal with complexities due to genderless connections and multi-DOF modules. Evaluations of repeatability of 6-DOF configuration are performed to prove that the performance of ModMan is comparable to existing non-reconfigurable manipulators. Experiments on reconfiguration of kinematics for arbitrary connections of modules are also demonstrated.